The seismic traffic footprint: Tracking trains, aircraft, and cars seismically. Issue 8 (19th April 2015) - Riahi, Nima; Gerstoft, Peter
Abstract Although naturally occurring vibrations have proven useful to probe the subsurface, the vibrations caused by traffic have not been explored much. Such data, however, are less sensitive to weather and low visibility compared to some common out‐of‐road traffic sensing systems. We study traffic‐generated seismic noise measured by an array of 5200 geophones that covered a 7 × 10 km area in Long Beach (California, USA) with a receiver spacing of 100 m. This allows us to look into urban vibrations below the resolution of a typical city block. The spatiotemporal structure of the anthropogenic seismic noise intensity reveals the Blue Line Metro train activity, departing and landing aircraft in Long Beach Airport and their acceleration, and gives clues about traffic movement along the I‐405 highway at night. As low‐cost, stand‐alone seismic sensors are becoming more common, these findings indicate that seismic data may be useful for traffic monitoring.